Design of Novel Metal Nanostructures for Broadband Solar Energy Conversion. (3rd February 2015) - Zhang, Kristine A.; Ma, David; Pu, Ying-Chih; Li, Yat
Abstract : Solar power holds great potential as an alternative energy source, but current photovoltaic cells have much room for improvement in cost and efficiency. Our objective was to develop metal nanostructures whose surface plasmon resonance (SPR) spectra closely match the solar spectrum to enhance light absorption and scattering. We employed the finite-difference time-domain simulation method to evaluate the effect of varying key parameters. A novel nanostructure with SPR absorption matching a region of the solar spectrum (300 to 1500 nm) that contains 90% of solar energy was successfully designed. This structure consists of a large gold-silica core-shell structure with smaller gold nanoparticles and nanorods on its surface. Such complex nanostructures are promising for broad and tunable absorption spectra. In addition, we investigated the SPR of silver nanoparticle arrays, which can achieve scattering close to the solar spectrum. We demonstrated an improvement in efficiency of over 30% with optimal nanoparticle radius and periods of 75 nm and 325 nm, respectively. In combination, our studies enable high-efficiency, tunable, and cost-effective enhancement of both light absorption and scattering, which has potential applications in solar energy conversion as well as biomedical imaging.